Production Planning in Assembly Line Systems - Chandrasekaran, R.; Aneja, Y. P.; Nair, K. P. K. (Management Science, 1984)
We develop a production planning model in the context of a system of assembly lines or production lines. The model is a large-scale linear program and we provide a polynomial column generation technique for its efficient solution. The column generation technique and the approach therein are also of interest in certain other problems. A numerical example to illustrate the algorithm is included. Finally computational experience with the algorithm is summarized.